Sensitive periods, language aptitude, and ultimate L2 attainment - Granena, Gisela; Long, Michael H. (Language learning and language teaching., 2013)
Research in second language acquisition has long posited that learners' individual differences affect ultimate attainment. This chapter reviews studies that examine how learners with differing cognitive aptitudes respond to instructional treatments. Most of these studies showed significant aptitude-by-treatment interactions (ATI), which suggest that the effectiveness of a particular type of instruction depends on stable, cognitive abilities, such as language analysis or working memory. From our review of this literature, we conclude that, although some interactions have been shown, there is still limited work using a rigorous ATI matched/mis-matched design. We therefore assess the strengths and weaknesses of existing ATI studies, as well as their practical implications, as it is our hope that future research will incorporate the necessary design elements to probe how tailoring instruction to individual cognitive aptitudes affects second language learning.